(untitled) (Bangladesh Pharmaceutical Journal, 2016)
The present study is focused towards the analysis of different barriers and prospects of pharmaceutical industries in Bangladesh. Pharmaceutical industry is one of the most promising sectors in Bangladesh. After the promulgation of local industry friendly Drug (Control) Ordinance in 1982 the scenario of pharmaceutical industries changed considerably. Now, after fulfilling the local demand Bangladesh is exporting pharmaceutical products to over 100 countries of the world. There are still lots of space for Bangladesh to flourish in this sector. So initiatives from the stakeholders are required to ensure the remarkable growth of pharmaceutical industries in Bangladesh. In this study, the scopes of advancement and the factors that can hinder the growth of pharmaceutical business are discussed thoroughly. Bangladesh Pharmaceutical Journal 19(1): 53-57, 2016